Ultra-processed foods and allergic symptoms among children and adults in the United States: A population-based analysis of NHANES 2005–2006 - Kong, Weiliang; Xie, Yilian; Zhong, Jingjing; Cao, Chao (Frontiers in Public Health, 2022)
Design: There is a strong correlation between dietary and allergic diseases. Ultra-processed foods are gradually becoming dominant worldwide and health problems for children and adults. We hope to determine if links exist between ultra-processed foods and allergic symptoms. Methods: Herein, we investigated data of 2736 children (≥6 years) and 4256 adults from the National Health and Nutritional Examination Survey (NHANES) 2005-2006. The mean UPFs contribution to total energy intake was assessed using two 24-h diet recalls according to the NOVA system. Allergic symptoms such as current asthma, allergy, rash, sneeze, wheeze, eczema, and hay fever were collected from self-reported questionnaires. Allergic sensitization was defined as a total IgE level of ≥150 kU/L. The associations were estimated by multivariate logistic regression models. Results：In this study, we found UPFs were significantly and negatively associated with IgE levels in children after adjusting for age, sex, race/ethnicity, tobacco exposure, mildew smell, furry animals, and cockroaches, compared with quartile 1 (lowest quartile), the ORs (95% CIs) of IgE from quartiles 2 to 4 were 0.84 (0.55,1.28), 0.68 (0.42,1.12) and 0.66 (0.49,0.89), p for trend= 0.006. We also found UPFs positively related to the prevalence of current asthma in children, with ORs (95% CIs) from quartiles 2 to 4 were 1.11 (0.79, 1.56), 1.12 (0.70, 1.80), and 1.76 (1.10, 2.82), p for trend = 0.0393. UPFs were also associated with eczema in female children. UPFs were not associated with allergic symptoms in adults. Conclusion: Our results suggested that UPFs assessed by NOVA system were associated with IgE, current asthma, and eczema of females in children. These results further support the need to test the association of modern dietary patterns with allergic symptoms.